Correlations of Single-Leg Performance Tests to Patient-Reported Outcomes After Primary Anterior Cruciate Ligament Reconstruction. Issue 5 (September 2021) - Roe, Chelsey; Jacobs, Cale; Kline, Paul; Lucas, Kathryn; Johnson, Darren; Ireland, Mary L.; Lattermann, Christian; Noehren, Brian
Abstract : Objective: To determine the relationship between patient-reported outcomes (PROs) to the single-leg step-down test (SLSD) and the Y-balance anterior reach (YB-A) 6 months after primary anterior cruciate ligament reconstruction (ACLR). Design: Cross-sectional. Setting: Laboratory. Participants: Sixty-six patients 6 months after ACLR participated. Interventions: Patients performed the SLSD, YB-A, and completed PROs after ACLR. Main Outcome Measures: Patients completed the International Knee Documentation Committee Score (IKDC), the Lysholm Activity Scale, the Tampa Scale of Kinesiophobia (TSK-11), and the Knee Injury and Osteoarthritis Outcome Score (KOOS)–Symptom, –Sport, and –Quality of Life (QOL) subscales. The SLSD requires subjects to complete as many single-leg step-downs as possible in 60 seconds, and the YB-A involves reaching anteriorly on a single limb. Pearson product moment correlations were used to assess relationships between the YB-A and SLSD performance to each PRO. Results: Single-leg step-down test symmetry was significantly correlated with the TSK-11 (r = −0.70), KOOS-Sport (r = 0.40), -Symptom (r = 0.46), and -QOL (r = 0.42). The YB-A symmetry was significantly correlated with the KOOS-Symptom (r = 0.30) and KOOS-Sport (r = 0.30). Conclusions: Single-leg step-down test performance demonstrated stronger relationships to patient-reported knee function than the YB-A. Furthermore, the SLSD symmetry was strongly correlated with fear of movement. The SLSD provides a robust method for clinicians to assess dynamic knee function and may aid in identifying patients who could benefit from intervention to reduce fear of movement or reinjury.